The Action of Prostaglandins on Ion Channels - Meves, Hans (Current Neuropharmacology, 2006)
Prostaglandins, in particular PGE2 and prostacyclin PGI2, have diverse biological effects. Most importantly, they are involved in inflammation and pain. Prostaglandins in nano- and micromolar concentrations sensitize nerve cells, i.e. make them more sensitive to electrical or chemical stimuli. Sensitization arises from the effect of prostaglandins on ion channels and occurs both at the peripheral terminal of nociceptors at the site of tissue injury (peripheral sensitization) and at the synapses in the spinal cord (central sensitization). The first step is the binding of prostaglandins to receptors in the cell membrane, mainly EP and IP receptors. The receptors couple via G proteins to enzymes such as adenylate cyclase and phospholipase C (PLC). Activation of adenylate cyclase leads to increase of cAMP and subsequent activation of protein kinase A (PKA) or PKA-independent effects of cAMP, e.g. mediated by Epac (=exchange protein activated by cAMP). Activation of PLC causes increase of inositol phosphates and increase of cytosolic calcium. This article summarizes the effects of PGE2, PGE1, PGI2 and its stable analogues on non-selective cation channels and sodium, potassium, calcium and chloride channels. It describes the mechanism responsible for the facilitatory or inhibitory prostaglandin effects on ion channels. Understanding these mechanisms is essential for the development of useful new analgesics.
Keywords: cAMP